Factors Associated with Skilled Birth Attendance in Nepal - Thapa, Naba Raj (Curriculum Development Journal, 2024)
The purpose of this study is to examine the prevalence and factors associated with skilled birth attendance among married women aged 15-49 years in Nepal. This study uses data from the Nepal Multiple Indicator Cluster Survey (MICS) 2019 and is a nationally representative cross-sectional survey. More than three-quarters of women had a skilled birth attendant at delivery. The prevalence of skilled birth attendance varies widely among women of demographic and socioeconomic backgrounds. Adjusted logistic regression analysis revealed that women in Sudurpaschim province, migrant women, women who attained secondary and higher education levels, women in poor, middle, rich, and richest household status, women with health insurance, and women who attended at least four ANC visits had higher odd of skilled birth attendance at delivery. Women with two, three, and four or more parity, women from the Terai caste, Muslim women, and women from Madhesh province had lower odds of skilled birth attendance at delivery. All programs and interventions should prioritize multifarious women, women from disadvantaged groups and low socio-economic status, and expansion of health insurance to improve skilled birth attendants at delivery.